Charpy Impact Testing and Hardness Evaluation of S355MC High-Strength Steel After Gleeble Modeling with Varied Cooling Times - Mkanna, Lama (Dunakavics, 2024)
High-strength steel alloys, like S355MC, are widely employed in structural and automotive applications, demanding a deep understanding of their behavior under different processing conditions. This study investigates the impact toughness and hardness of S355MC steel samples after Gleeble modeling, a thermomechanical simulation technique. The cooling time, a critical factor in microstructural development, is varied to explore its influence on mechanical properties. Charpy impact testing and Vickers hardness measurements were performed to assess the steel’s response to different cooling conditions. The research includes a series of S355MC steel specimens, each subjected to Gleeble modeling under distinct cooling times. Charpy impact tests, following ASTM standards, reveal the steel’s ability to withstand sudden loading and its energy absorption capacity. The results show that with shorter cooling times, the impact energy absorption capacity of the steel decreases. Vickers hardness tests provide information on the material’s resistance to localized plastic deformation and its suitability for specific applications. The findings reveal that the hardness of S355MC increases with reduced cooling times, indicating a relationship between microstructure and hardness. This study highlights the significance of cooling time control in the heat treatment process for S355MC steel. The insights obtained from the impact and hardness testing are essential for optimizing processing conditions, ensuring the steel’s reliability in applications where impact resistance and hardness are vital.